Analisis Indeks Erosivitas Hujan menggunakan Metode Bols dan Utomo (Studi Kasus: Sub DAS Way Pubian, Das Way Seputih, Provinsi Lampung) - Agestia, Lady; Romdania, Yuda; Ashruri, Ashruri; Herison, Ahmad (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2023)
Indonesia has a tropical climate which results in high rainfall throughout the year. The high rainfall makes Indonesia prone to erosion. The ability of rainfall to cause erosion is called rainfall erosivity. The study aims to calculate the rainfall erosivity index in the Way Pubian Subwatershed area by comparing the Bols and Utomo methods. The research methods used include; data consistency test, rainfall analysis, and calculation of rainfall erosivity index. Based on several studies on the erosivity index, in the Indonesian region the calculation of the Bols Method erosivity index often gets a higher value than the Utomo Method because the data used for the calculation of the Bols Method requires more data than the Utomo Method which only uses monthly rainfall data. The conclusion is that the Bols Method erosivity index value is 2651.2120 and the Utomo Method is 1008.3435, the Bols Method erosivity index value is higher than the Utomo Method value with an interval of 1642.8685. The use of the Bols equation to calculate the erosivity index value is considered safer to use in estimating the erosion rate. Keywords: Bols, Rainfall Erosivity, Sub Das Way Pubian, Utomo